In-situ Synthesis of MnO2@Graphdiyne Oxides Nanocomposite with Enhanced Performance of Supercapacitors. (10th October 2017) - Xu, Jing; Li, Jiaqiang; Yang, Qiaoling; Xiong, Yan; Chen, Changguo
Graphical abstract: Abstract: An in-situ synthetic route is designed to prepare manganese dioxide (MnO2 ) nanosphere supported on graphdiyne oxides (GDYO) that is applied as electrode material for supercapacitors. The electrochemical measurements reveal that the MnO2 @GDYO composite has a specific capacitance of 301 and 170 F g −1 at the current density of 0.2 and 10 A g −1, which is prior to the supercapacitor performance of MnO2 @GDY. The cyclic stability test presents that MnO2 @GDYO has a 98% initial capacitance retention even after 3000 charge-discharge cycles. The attractive supercapacitor performance of the composite material MnO2 @GDYO make it potentially a promising candidate for future energy storage systems.